PENGARUH WAKTU PENAHANAN PROSES SINTERING TERHADAP NILAI KEKERASAN PRODUK EKSTRUSI PANAS DARI BAHAN BAKU GERAM ALUMINIUM HASIL PROSES PERMESINAN - Bagus Sigit Pambudi; Rusnaldy Rusnaldy; Norman Iskandar (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
This research have a purpose to find out effect of hold time in sintering process about density, hardness value and microstructure from recycling aluminium with powder metallurgy process. Aluminium rod is on turning process produce aluminium chips and then is milling process produce powder with mesh 40. Compaction of aluminium powder until reach the green density with 20 mm length and 14 mm diameter continue with heating or sintering temperature is 350°C during 2, 3, 4, and 5 hours and then the specimen is extrude from 14 mm to 12 mm of diameter. Density and hardness value of aluminium with powder metallurgy process is examination. Result is indicate the longer time of hold time in sintering, density value is increase but hardness value is decrease and increase or coarsening of grain size.